Low-viscosity easy-to-tear protective film and preparation method thereof
By using specific modified monomers and initiators in the protective film, the problems of increased peeling force and viscosity of the existing protective film are solved, and the preparation of a low-viscosity, easy-to-tear protective film is achieved, which has good high temperature resistance and easy-to-tear properties. performance.
Patent Information
- Application Number
- CN202411644646.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
AI Technical Summary
The peeling force of the existing protective film increases over time and the glue increases stickiness, making it difficult to achieve easy tear effect.
By using modified monomers compounded with 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkyl ethyl methacrylate, the structural stability of the polymer and the high temperature resistance of the adhesive layer are improved. At the same time, 3-carboxybenzoyl lactate is used as the initiator to optimize the cross-linking density and cohesion of the glue to achieve a synergistic effect of bonding firmness and easy tearing performance.
The preparation of low viscosity is easy to tear the protective film. The glue layer has improved structural stability and high temperature resistance. At the same time, it has good adhesion firmness and tear performance.
Smart Images

Figure BDA0005139382490000081 
Figure BDA0005139382490000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of protective films, and in particular to a low-viscosity easy-to-tear protective film and a preparation method thereof. Background Art
[0002] Protective films are widely used in many industries, especially in electronics, packaging, optics and construction. Protective films are usually composed of a substrate layer and an adhesive layer. Over time, the peeling force will increase and the adhesive will become more viscous, which will prevent the film from being easily torn.
[0003] Therefore, it is necessary to improve the low-viscosity protective film in the prior art. Summary of the invention
[0004] One of the purposes of the present invention is to overcome the defects existing in the prior art and provide a low-viscosity easy-to-tear protective film. The modified monomers of 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate are compounded to improve the structural stability of the polymer and the high-temperature resistance of the adhesive layer, and the synergistic effect improves the adhesion firmness of the adhesive layer while achieving easy-to-tear performance; 3-carboxybenzoyl lactylate has the same ester group compatibility with the glue polymer, the initiation rate is improved, and the crosslinking density and cohesion between the monomers in the glue are optimized.
[0005] In order to achieve the above-mentioned process effect, the technical solution of the present invention is: a low-viscosity easy-to-tear protective film, comprising a substrate layer, a low-viscosity layer and a release film stacked in sequence, wherein the glue of the low-viscosity layer comprises a polymerized monomer, a cross-linking monomer, a modified monomer, an emulsifier, an initiator and deionized water;
[0006] The modified monomers are 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate;
[0007] The initiator is 3-carboxybenzoyl lactylate.
[0008] The preferred technical solution is: the polymerizable monomers include soft monomers and hard monomers. Calculated by weight, the glue includes 70-80 parts of soft monomers, 6-12 parts of hard monomers, 5-10 parts of cross-linking monomers, 4-8 parts of modified monomers, 1-4 parts of emulsifiers, 1-1.5 parts of initiators and 100-120 parts of deionized water.
[0009] The preferred technical solution is: the mass ratio of 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate is (4-5):(1-2):1.
[0010] The preferred technical solution is: the soft monomer is isooctyl acrylate and / or butyl acrylate, and the hard monomer is methyl methacrylate.
[0011] The preferred technical solution is: the cross-linking monomers are acrylic acid and hydroxyethyl acrylate; further, the mass ratio of acrylic acid to hydroxyethyl acrylate is (1-2):1.
[0012] The preferred technical solution is: the emulsifier is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and octylphenol polyoxyethylene ether.
[0013] The preferred technical scheme is: the preparation of the initiator: tert-butyl 2-bromopropionate is added dropwise to a solution of isophthalic acid, reacted under the action of a first alkali solution at 50-60° C. to obtain tert-butyl 3-carboxybenzoyl lactate, then reacted with trifluoroacetic acid in an ice bath for purification, and then a second alkali solution is added to obtain 3-carboxybenzoyl lactate.
[0014] The second object of the present invention is to overcome the defects in the prior art and provide a method for preparing a low-viscosity easy-to-tear protective film, comprising the following steps:
[0015] S1: mixing a polymerizable monomer, 4-acryloylmorpholine, an emulsifier and deionized water to obtain a first emulsion; mixing a polymerizable monomer, a cross-linking monomer, N,N-dimethylacrylamide, an emulsifier and deionized water to obtain a second emulsion; mixing a polymerizable monomer, a cross-linking monomer, perfluoroalkylethyl methacrylate, an emulsifier and deionized water to obtain a third emulsion;
[0016] S2: dividing the initiator into a first initiator, a second initiator and a third initiator;
[0017] S3: adding the first initiator to the first emulsion and mixing, heating the first stage to a stable temperature, and keeping the temperature to react to obtain a first polymerization reaction liquid;
[0018] S4: the first polymerization reaction liquid is heated to a stable temperature after the second stage, the second emulsion and the second initiator are mixed, and the mixture is added dropwise to the first polymerization reaction liquid to be heated and reacted, thereby obtaining a second polymerization reaction liquid;
[0019] S5: the third emulsion and the third initiator are mixed and added dropwise to the second polymerization reaction liquid to react and obtain a polymerized glue liquid;
[0020] S6: coating the polymerized adhesive on the surface of the substrate layer and curing the polymerized adhesive to obtain a protective film having a low-adhesive layer.
[0021] The preferred technical solution is: the mass ratio of the polymerization monomers in the first emulsion, the second emulsion and the third emulsion is 1:(1-2):(1-3); the mass ratio of the cross-linking monomers in the second emulsion and the third emulsion is 1:(1-3); the mass ratio of the first initiator, the second initiator and the third initiator is (5-10):(30-40):(50-60).
[0022] The preferred technical solution is: the first stage is heated to 70-75°C, the second stage is heated to 79-82°C; the curing temperature is 70-80°C.
[0023] The advantages and beneficial effects of the present invention are:
[0024] The low-viscosity easy-to-tear protective film uses a modified monomer compounded with 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate to improve the cohesive force of the latex in the adhesive solution from the inside out, thereby improving the structural stability of the polymer and the high-temperature resistance of the adhesive layer, and synergistically improves the bonding firmness of the adhesive layer while achieving easy-to-tear performance;
[0025] 3-Carboxybenzoyl lactate has good compatibility with the same ester group as the glue polymer, improves the initiation rate, optimizes the cross-linking density and cohesion between the monomers in the glue, and the free radicals generated by the fracture all contain ester groups, and no by-products are produced to bring negative effects on the polymer properties of the glue. DETAILED DESCRIPTION
[0026] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.
[0027] Polymerization monomer
[0028] Soft monomers, also known as viscous monomers, are the main monomers for preparing pressure-sensitive adhesives. Soft monomers are mainly alkyl acrylates with carbon atoms ranging from 4 to 12. The advantages are low glass transition temperature and good initial adhesion. Soft monomers include but are not limited to ethyl acrylate, butyl acrylate and isooctyl acrylate. Further, the soft monomer is isooctyl acrylate, or a combination of isooctyl acrylate and butyl acrylate. Furthermore, the mass ratio of isooctyl acrylate to butyl acrylate is 1:(1 to 1.2).
[0029] Hard monomers are also called cohesive monomers, mainly acrylates or other olefin monomers. They play the role of producing homopolymers with higher glass transition temperatures and copolymerizing with soft monomers. Hard monomers include but are not limited to methyl acrylate, methyl methacrylate, vinyl acetate and styrene. Further, the hard monomer is methyl methacrylate.
[0030] Crosslinking monomers, also called functional monomers, refer to vinyl monomers with various reactive functional groups that can copolymerize with soft monomers and hard monomers. Crosslinking monomers include, but are not limited to, acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, acrylamide, methacrylamide, maleic acid and maleic anhydride. Further, the crosslinking monomers are acrylic acid and hydroxyethyl acrylate. Further, the mass ratio of acrylic acid to hydroxyethyl acrylate is (1-2):1. Further, the mass ratio of acrylic acid to hydroxyethyl acrylate is (1.5-2):1.
[0031] Modified monomers give the adhesive layer better adhesion, heat resistance, tensile strength, water resistance and stain resistance. 4-Acryloylmorpholine (ACMO) has a larger six-membered ring on the side chain, which enhances the mutual entanglement between molecular chains, thereby improving the shear resistance of the pressure-sensitive adhesive, so the adhesion is improved. The amide group N element has a strong H absorption capacity, which increases the hydrogen bonding between polymer chains, and adds an additional cross-linked network structure between polymer chains, which can further improve the high temperature resistance of the adhesive layer. In the molecular structure of N, N-dimethylacrylamide (NNDMA), the two H atoms on the amide group N atom are replaced by hydrophobic methyl groups, thereby improving the hydrolytic stability of the adhesive. The amide group can increase the hydrogen bonding between polymer chains, thereby improving the cohesive force of the adhesive. Too high ammonia has a negative effect on the high temperature resistance of the adhesive layer; it also helps to improve the fluidity and coating uniformity of the adhesive, making it easier for the adhesive to form a continuous and smooth coating on the substrate layer. Perfluoroalkylethyl methacrylate improves the chemical resistance, water resistance, oil resistance and surface performance of the adhesive layer. In order to maintain sufficient viscosity for a period of time to ensure that the protective film does not fall off, and at the same time, it will not leave residual glue or damage the protected surface when removed, the perfluoroalkyl chain is C4~C8, which can provide a better balance, with a certain degree of hydrophobicity and oleophobicity, and will not affect the bonding performance too much. In order to improve the utilization rate of perfluoroalkylethyl methacrylate, it is added in the late stage of the polymerization reaction, so that the perfluoroalkylethyl methacrylate is concentrated on the surface of the latex particles. In the emulsion state, the perfluoroalkylethyl methacrylate can better protect the latex particles and further improve the chemical and hydrolytic stability of the latex particles. In the process of film formation of the glue liquid, the perfluoroalkylethyl methacrylate can also more easily move to the surface of the film to improve the modification effect.
[0032] Initiator
[0033] Preparation of 3-carboxybenzoyl lactate: 10% NaOH was added dropwise to isophthalic acid in a molar ratio of 1:1, the temperature was raised to 55°C and stirred for 60 min, 2-bromopropionic acid tert-butyl ester was added dropwise in an equal molar ratio to isophthalic acid, and tert-butyl 3-carboxybenzoyl lactate was obtained after reaction for 2 h. The reaction solution was purified and trifluoroacetic acid was added dropwise in an ice bath to react for 6 h. After purification again, NaOH was added to obtain sodium 3-carboxybenzoyl lactate.
[0034] 3-Carboxybenzoyl lactate initiator is suitable for aqueous solutions, has high initiation efficiency and is environmentally friendly.
[0035] Example 1
[0036] The low-viscosity easy-to-tear protective film includes a substrate layer, a low-viscosity layer and a release film stacked in sequence. The substrate layer is made of a coextruded polyethylene film, the film thickness of the substrate layer is 40 to 60 μm, the thickness of the low-viscosity layer is 12 to 20 μm, and the glue of the low-viscosity layer includes a polymerized monomer, a cross-linked monomer, a modified monomer, an emulsifier, an initiator and deionized water; the modified monomer is 4-acryloylmorpholine, N, N-dimethylacrylamide and perfluoroalkylethyl methacrylate. The initiator is 3-carboxybenzoyl lactate. Among them, the polymerized monomer includes a soft monomer and a hard monomer, the soft monomer is isooctyl acrylate and butyl acrylate in a mass ratio of 1:1.2, the hard monomer is methyl methacrylate, and the cross-linked monomer mass ratio is acrylic acid and hydroxyethyl acrylate in a ratio of 1.8:1. The mass ratio of 4-acryloylmorpholine, N, N-dimethylacrylamide and perfluoroalkylethyl methacrylate is 4.5:1.5:1. Among them, the fluoroalkyl chain is C6, that is, perfluorohexylethyl methacrylate. The emulsifier is sodium lauryl sulfate.
[0037] The method for preparing the low-viscosity easy-to-tear protective film comprises the following steps:
[0038] S1: mixing a polymerizable monomer, 4-acryloylmorpholine, an emulsifier and deionized water to obtain a first emulsion; mixing a polymerizable monomer, a cross-linking monomer, N,N-dimethylacrylamide, an emulsifier and deionized water to obtain a second emulsion; mixing a polymerizable monomer, a cross-linking monomer, perfluoroalkylethyl methacrylate, an emulsifier and deionized water to obtain a third emulsion;
[0039] S2: dividing the initiator into a first initiator, a second initiator and a third initiator;
[0040] S3: Add the first initiator to the first emulsion and mix them. The first initiator is added for 0.5 h, the stirring speed is 210 r / min, the temperature is raised to 72° C. for 1 h, and the temperature is kept for 2 h to obtain the first polymerization reaction liquid.
[0041] S4: The first polymerization reaction liquid is heated to 80°C in the second stage, the second emulsion and the second initiator are mixed and added dropwise to the first polymerization reaction liquid for 1 hour, the stirring speed is 240r / min, and the temperature is kept for 2 hours to obtain the second polymerization reaction liquid;
[0042] S5: The third emulsion and the third initiator are mixed and added dropwise to the second polymerization reaction solution for reaction. The dropping time is 0.5 h, the stirring speed is 200 r / min, and the temperature is kept for reaction for 2 h to obtain a polymerized glue solution.
[0043] S6: coating the polymerized adhesive on the surface of the substrate layer and curing the polymerized adhesive to obtain a protective film having a low-adhesive layer at a curing temperature of 75°C.
[0044] Among them, by weight, the glue includes 75 parts of soft monomer, 8.8 parts of hard monomer, 7 parts of cross-linking monomer, 5 parts of modified monomer, 3 parts of emulsifier, 1.2 parts of initiator and 120 parts of deionized water. The mass ratio of polymerized monomers in the first emulsion, the second emulsion and the third emulsion is 1:1.2:2.8; the mass ratio of cross-linking monomers in the second emulsion and the third emulsion is 1:1.5; the mass ratio of the first initiator, the second initiator and the third initiator is 6:34:60.
[0045] Example 2
[0046] Example 2 is based on Example 1, except that, by mass, the glue includes 75 parts of soft monomer, 8.8 parts of hard monomer, 7 parts of cross-linking monomer, 4 parts of modified monomer, 3 parts of emulsifier, 1.2 parts of initiator and 120 parts of deionized water.
[0047] Example 3
[0048] Example 3 is based on Example 1, except that, by weight, the glue includes 75 parts of soft monomer, 8.8 parts of hard monomer, 7 parts of cross-linking monomer, 8 parts of modified monomer, 3 parts of emulsifier, 1.2 parts of initiator and 120 parts of deionized water.
[0049] Example 4
[0050] Example 4 is based on Example 1, except that, based on mass fractions, the composition of the glue solution remains unchanged, and the mass ratio of 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate is 3:1.8:1.
[0051] Example 5
[0052] Example 5 is based on Example 1, except that, based on mass fractions, the composition of the glue solution remains unchanged, and the mass ratio of 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate is 7:1.8:1.
[0053] Example 6
[0054] Example 6 is based on Example 1, except that, based on mass fractions, the composition of the glue solution remains unchanged, and the mass ratio of 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate is 4.5:0.5:1.
[0055] Example 7
[0056] Example 7 is based on Example 1, except that the composition of the glue solution remains unchanged, S3 and S4 are combined, that is, the first emulsion and the second emulsion are not reacted step by step, the reaction temperature is 80°C, the first initiator and the second initiator are mixed and added dropwise, and the addition time is 1.5h, the stirring speed is 210r / min, and the reaction is kept warm for 3h; other steps remain unchanged.
[0057] Example 8
[0058] Example 8 is based on Example 1, except that the first emulsion also contains a cross-linking monomer, and the mass ratio of the cross-linking monomer in the first emulsion, the second emulsion and the third emulsion is 0.5:1:1.
[0059] Example 9
[0060] Example 9 is based on Example 1, except that S4 and S5 are combined, that is, the second emulsion and the third emulsion are not reacted step by step, the second emulsion, the third emulsion, the second initiator and the third initiator are uniformly mixed, and added dropwise to the first polymerization reaction liquid. The reaction temperature is 80°C, the dropping time is 1.5h, the stirring speed is 240r / min, and the reaction is kept warm for 3h; the other steps remain unchanged.
[0061] Comparative Example 1
[0062] Comparative Example 1 is based on Example 1, except that the modified monomer only includes N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate, and the other compositions and process steps remain unchanged.
[0063] Comparative Example 2
[0064] Comparative Example 2 is based on Example 1, except that the modified monomers only include 4-acryloylmorpholine and perfluoroalkylethyl methacrylate, and the other compositions and process steps remain unchanged.
[0065] Comparative Example 3
[0066] Comparative Example 3 is based on Example 1, except that the modifying monomer is only perfluoroalkylethyl methacrylate.
[0067] Comparative Example 4
[0068] Comparative Example 4 is based on Example 1, except that the initiator is potassium persulfate, and other conditions remain unchanged.
[0069] Performance Test:
[0070] 1. High temperature resistance: stick a 25mm wide and 50mm long protective film on a standard stainless steel test plate, pressurize it with 20 kg and put it in an oven, heat it to 80°C, and bake it for 72 hours (simulating outdoor weathering for 3 months). After baking, cool it naturally indoors for 12 hours to room temperature, and compare the peeling force data with the initial adhesion peeling force data to calculate the viscosity increase of the glue: (peeling force after high temperature - peeling force before high temperature) / peeling force before high temperature * 100%.
[0071] 2. Easy-tear peeling strength: stick a protective film with a width of 25mm and a length of 50mm on a standard stainless steel test plate, then apply 50kg of pressure on the surface of the base layer of the protective film and place it in a room at about 20℃ for one week (simulating the easy-tear effect of the protective film after heavy pressure from container handling).
[0072] The performance tests of the embodiments and comparative examples are as follows:
[0073]
[0074]
[0075] Compared with Example 1, in Example 3, as the modified monomer increases, the polymerization cross-linking cohesion increases, the viscosity of the adhesive increases, and the tearability of the adhesive layer is negatively affected.
[0076] Compared with Example 1, as the 4-acryloylmorpholine in the modified monomer decreases, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate increase, the initial adhesion peeling force, i.e. the peeling force before high temperature, decreases, the cohesive force of the latex in the adhesive solution from the inside to the outside is unbalanced, and N,N-dimethylacrylamide increases, resulting in a decrease in the high temperature resistance of the adhesive layer.
[0077] Compared with Example 1, as the content of 4-acryloylmorpholine in the modified monomer increases, the content of N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate decreases, which has a negative impact on the tearability of the adhesive layer.
[0078] Compared with Example 1, as the content of 4-acryloylmorpholine and perfluoroalkylethyl methacrylate in the modified monomers increases and N,N-dimethylacrylamide decreases, the cohesive force of the latex in the adhesive is unbalanced from the inside to the outside and the leveling of the adhesive is poor, which has a negative impact on the high temperature resistance of the adhesive layer.
[0079] Compared with Example 1, in Example 7, the first emulsion and the second emulsion are not polymerized in steps, so that the viscosity of the adhesive is too high and difficult to control, which has a negative impact on the high temperature resistance and tearability of the adhesive layer.
[0080] Compared with Example 1, Example 8 contains cross-linking monomers in the first emulsion, which makes the core cross-linking density of the latex larger, the cohesive force increases, and the viscosity also increases, which is not conducive to the dispersion of the second emulsion and the third emulsion. In addition, the cross-linking monomers in the second emulsion and the third emulsion are reduced, and the attachment points of the formed core-shell outside the core are reduced, which has a negative impact on the stability of the glue liquid and has a negative impact on the high temperature resistance and tearability of the resulting glue layer.
[0081] Compared with Example 1, in Example 9, the second emulsion and the third emulsion are not polymerized in steps, and the cross-linking polymerization of the monomers in the adhesive is difficult to control, resulting in a reduction of perfluoroalkylethyl methacrylate on the surface of the latex, which has a negative impact on the tearability.
[0082] Compared with Example 1, in Comparative Example 1, Comparative Example 2 and Comparative Example 3, the adhesive layer obtained by compounding 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate has the best performance.
[0083] Compared with Example 1, in Comparative Example 4, when the initiation time and temperature remain unchanged, the initiation efficiency of the potassium persulfate initiator is reduced, resulting in incomplete polymerization of the monomers, which has a negative impact on the high temperature resistance and tearability of the obtained adhesive layer, and there is residual adhesive.
[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A low-viscosity easy-to-tear protective film, comprising a substrate layer, a low-viscosity layer and a release film stacked in sequence, characterized in that: The adhesive solution of the low-viscosity layer includes polymerized monomers, cross-linked monomers, modified monomers, emulsifiers, initiators and deionized water; The modified monomers are 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate; The initiator is 3-carboxybenzoyl lactylate.
2. The low-viscosity easy-tear protective film according to claim 1, characterized in that: The polymerizable monomers include soft monomers and hard monomers. Calculated by weight, the glue includes 70-80 parts of soft monomers, 6-12 parts of hard monomers, 5-10 parts of cross-linking monomers, 4-8 parts of modified monomers, 1-4 parts of emulsifiers, 1-1.5 parts of initiators and 100-120 parts of deionized water.
3. The low-viscosity easy-tear protective film according to claim 1 or 2, characterized in that: The mass ratio of 4-acryloylmorpholine, N,N-dimethylacrylamide and perfluoroalkylethyl methacrylate is (4-5): (1-2):
1.
4. The low-viscosity easy-tear protective film according to claim 2, characterized in that: The soft monomer is isooctyl acrylate and / or butyl acrylate, and the hard monomer is methyl methacrylate.
5. The low-viscosity easy-tear protective film according to claim 1 or 2, characterized in that: The cross-linking monomers are acrylic acid and hydroxyethyl acrylate; further, the mass ratio of acrylic acid to hydroxyethyl acrylate is (1-2):
1.
6. The low-viscosity easy-tear protective film according to claim 1 or 2, characterized in that: The emulsifier is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and octylphenol polyoxyethylene ether.
7. The low-viscosity easy-tear protective film according to claim 1, characterized in that: Preparation of the initiator: 2-bromopropionic acid tert-butyl ester is added dropwise to a solution of isophthalic acid, reacted under the action of a first alkali solution at 50-60°C to obtain 3-carboxybenzoyl lactylate, then reacted with trifluoroacetic acid in an ice bath for purification, and then a second alkali solution is added to obtain 3-carboxybenzoyl lactylate.
8. A method for preparing a low-viscosity easy-to-tear protective film, characterized in that: The following steps are involved: S1: mixing a polymerizable monomer, 4-acryloylmorpholine, an emulsifier and deionized water to obtain a first emulsion; mixing a polymerizable monomer, a cross-linking monomer, N,N-dimethylacrylamide, an emulsifier and deionized water to obtain a second emulsion; mixing a polymerizable monomer, a cross-linking monomer, perfluoroalkylethyl methacrylate, an emulsifier and deionized water to obtain a third emulsion; S2: dividing the initiator into a first initiator, a second initiator and a third initiator; S3: adding the first initiator to the first emulsion and mixing, heating the first stage to a stable temperature, and keeping the temperature to react to obtain a first polymerization reaction liquid; S4: the first polymerization reaction liquid is heated to a stable temperature after the second stage, the second emulsion and the second initiator are mixed, and the mixture is added dropwise to the first polymerization reaction liquid to be heated and reacted, thereby obtaining a second polymerization reaction liquid; S5: the third emulsion and the third initiator are mixed and added dropwise to the second polymerization reaction liquid to react and obtain a polymerized glue liquid; S6: coating the polymerized adhesive on the surface of the substrate layer and curing the polymerized adhesive to obtain a protective film having a low-adhesive layer.
9. The method for preparing a low-viscosity easy-tear protective film according to claim 8, characterized in that: The mass ratio of the polymerizable monomers in the first emulsion, the second emulsion and the third emulsion is 1:(1-2):(1-3); the mass ratio of the crosslinking monomers in the second emulsion and the third emulsion is 1:(1-3); the mass ratio of the first initiator, the second initiator and the third initiator is (5-10):(30-40):(50-60).
10. The method for preparing a low-viscosity easy-tear protective film according to claim 8, characterized in that: The first stage is heated to 70-75°C, and the second stage is heated to 79-82°C; the curing temperature is 70-80°C.